Consumer Motivation Moderates the Influence of Product Quality and Brand on Consumer Satisfaction in Shopee E-Commerce Users - Abdullah Zailani; Ahmad Dzulfikri Budi Kusworo (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The object of this research is Jemur Wonosari E-Commerce Users. The population in this study was 350 respondents. Meanwhile, the sample in this research consisted of 78 E-Commer consumer respondents. The purpose of this research was to test and analyze the influence of product quality on consumer satisfaction, to test and analyze the influence of product brands on consumer satisfaction, to test and analyze motivation moderating product quality on consumer satisfaction, to test and analyze the moderating motivation of product brands on consumer satisfaction. This research is quantitative research. The analysis technique in this research uses partial last square. The results of testing hypothesis 1 show that product quality has a significant effect on consumer satisfaction, the results of testing hypothesis 2 show that product brand has a significant effect on consumer satisfaction, the results of hypothesis 3 show that consumer motivation moderates product quality and has a significant effect on consumer satisfaction, while the results of testing hypothesis 4 show that Consumer motivation moderates product brand and has a significant effect on consumer satisfaction.